Perception citizen security in the district of Magdalena del Mar, Lima 2018 - Tamara Tamariz, Stalein J. (2019)
The present study was carried out to determine the factors related to the employability of graduates of the university gastronomy career offered by the Le Cordon Bleu University in Lima, Peru. The population was comprised of 50 professors, 300 students from the last two cycles of the gastronomy career, 216 graduates and 83 potential employers in the city of Lima. The sample was determined at random: 114 students and 27 teachers, and graduates and employers in an unrestricted sample. Surveys were applied in person in the case of teachers and students, and virtual in the case of graduates and employers.It was concluded that the main factors were: 1) The factors under the students' perception are: that you always like to keep harmony with your classmates, believing that you will be a good professional if you get a job in your career, criminal records and judicial, adapting easily to new technological changes, respect for nature, and almost always dependence on the quality of a job has the logistics it provides; 2) The factors under the perception of the graduates were always the acceptance of their responsibility in the face of an error made, having an organized plan to find a job, marital status, knowing how to negotiate and resolve conflicts, demonstrating affection for their peers , and the dependence that the quality of a job has on the skill of the worker; 3) The factors under the teachers' perception were mostly good respect for the environment, management of technological tools, having a leader profile, being supportive and showing management of their emotions in complicated situations; 4) The factors under the employers' perception were mostly good to be ordered in their activities and the performance in the presentations of entrusted work.For the most part employers considered that graduates required training and this training should be in soft skills, more efficient behavior in the area of work, languages, and ability to synthesize and analyze.